Effect of Seeding Rate On Growth And Yield Of Okra (Abelmoschus Esculantus) In Zuru Northern Guinea Savanna Of Nigeria - J, A., Yohanna; A, M., Muhammad (International Journal of Scientific Research and Management (IJSRM), 2018)
Field experiment was carried out during 2010 rainy season to find the effect of seeding rate on the growth and yield of okra (Abelmuschus esculentus) in Zuru Northern Guinea Savannah. Zuru is located in Zuru Local government area of Kebbi State (Latitude 11o 251 to 11o 551 North and Longitude 4o 51 to 5o 251 East of the equator). The experiment consisted of three treatments that is planting okra at one plant per stand (S1), two plants per stand (S2) and three plants per stand (S3). The experiment was laid out in randomized complete block design (RCBD) and the treatments replicated three time. The result of the experiment has shown that plant height and number of leaves/plant at 3, 6 and 9 weeks after planting (    WAP) were significantly influenced by seeding rate (P